2018
DOI: 10.1103/physrevb.98.045401
|View full text |Cite
|
Sign up to set email alerts
|

Coupled charge and spin dynamics in high-density ensembles of nitrogen-vacancy centers in diamond

Abstract: We studied the spin depolarization of ensembles of nitrogen-vacancy (NV) centers in nitrogenrich single crystal diamonds. We found a strong dependence of the evolution of the polarized state in the dark on the concentration of NV centers. At low excitation power, we observed a simple exponential decay profile in the low-density regime and a paradoxical inverted exponential profile in the high-density regime. At higher excitation power, we observed complex behavior, with an initial sharp rise in luminescence si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 46 publications
5
52
1
Order By: Relevance
“…It was demonstrated that an ensemble of NV centers could be stable enough to be used as a charge based data storage medium [23,24]. Other studies on dense ensembles of NVs and near-surface single NVs reported a strong interplay between charge and spin dynamics during illumination as well as in the dark that can interfere with spin measurements [13,25,26]. Disentangling the two contributions is critical to understand the underlying physical mechanisms, and to enable effective control of charge dynamics in many applications.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that an ensemble of NV centers could be stable enough to be used as a charge based data storage medium [23,24]. Other studies on dense ensembles of NVs and near-surface single NVs reported a strong interplay between charge and spin dynamics during illumination as well as in the dark that can interfere with spin measurements [13,25,26]. Disentangling the two contributions is critical to understand the underlying physical mechanisms, and to enable effective control of charge dynamics in many applications.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst recombination may not factor in this work, ionization of the NVcharge state may be an important factor particularly owing to the CW illumination used. Indeed, ionization of NVis known to be a function of optical illumination time 54 and illumination intensity 55 .…”
Section: Discussionmentioning
confidence: 99%
“…This is considered bearing in mind that the long-range structural and electronic perturbations that could occur for concentrations approaching this value may further decrease this limit, especially when considering the presence of neighbouring non-N-V − defects, such as 14/15 N and 13 C atoms. For example, in light of the N-V − systems unique charge-state dynamics [33], a finite concentration of electron donors, such as the 14/15 N defect, is necessary to ensure that the N-V − → N-V 0 conversion rate is negligible. Therefore, their relative density may also encourage the formation of aggregates and further limit the electronic integrity-retaining concentration.…”
Section: A Density Considerationsmentioning
confidence: 99%
“…Exceptionally, there are reports of concentrations exceeding 10 ppm and approaching 100 ppm [31][32][33]. This encourages the consideration of higher concentrations, and the optimistic outlook that there are no intrinsic limitations, as growth optimisation techniques and N-V − creation efficiencies are continuously improved.…”
Section: Introductionmentioning
confidence: 99%